Structural, microstructural and electrical properties of La0.67(Ba,Sr)0.33MnO3 system - Gan, Albert Han Ming; Lim, Kean Pah; Chen, Soo Kien; Talib, Zainal Abidin; Wong, Jen Kuen (American Institute of Physics, 2010)
La0.67(Ba,Sr)0.33MnO3 were prepared via solid‐state reaction method. Rietveld refinement showed that when Ba2+(1.49Å) is replaced with smaller ion, Sr2+(1.32Å), its lattice parameter, volume, bond distance and angle decreases, and also different microstructure was obtained. Transition temperature, Tp shifted to higher temperature while the resistance and magnetoresistance (MR) behaviour of samples were quite similar. This phenomenon believed to be due to the variation of spin‐dependent scattering and/or spin‐polarization tunneling across the grain surface/boundary. Typical polycrystalline (intrinsic and extrinsic MR) type of MR is shown for both samples. The highest % of low‐field magnetoresistance (LFMR) (at 0.1T) of ‐11.5% and ‐10.2% at 80 K was given by La0.67Ba0.33MnO3 (LBMO) and La0.67Sr0.33MnO3 (LSMO) samples respectively.